Incidence, risk factors, management and prevention of severe postoperative epistaxis after endoscopic endonasal transsphenoidal surgery: a single center experience - Liu, Xiaohai; Wang, Pengfei; Li, Mingchu; Chen, Ge (Frontiers in Surgery, 2023)
Objective: Postoperative epistaxis is a very rare but severe complication after endoscopic endonasal transsphenoidal surgery (EETS) that can lead to catastrophic consequences. However, the incidence, risk factors, management and prevention of postoperative epistaxis remain unclear.Patients and Methods: Consecutive patients with pituitary adenoma (PA), Rathke's cleft cyst, craniopharyngioma, or clival chordoma who received EETS in our department between September 2020 and November 2022 were retrospectively analyzed. The incidence, risk factors, management and prevention of postoperative epistaxis were investigated and analyzed.Results: A total of 557 consecutive patients who received EETS were included in this study.Eight patients (1.4%) (7 PAs and 1 Rathke's cleft cyst) experienced severe postoperative epistaxis. The size of the PAs was 9.6 mm to 46.2 mm, with a median size of 22.1 mm. Epistaxis occurred 4 hours to 30 days (median 14.5 days) postoperatively. Bleeding was stopped in 3 patients after nasal packing with iodoform gauze. The remaining 5 patients for whom nasal packing was insufficient were all sent to the operating room, and posterior nasal septal artery (PNSA) bleeding was identified and successfully treated with endoscopic bleeding artery electrocauterization under general anesthesia. In the EETS, all 8 patients had downward extension of the septal mucosal incision, in which 6 had intraoperative bleeding of PNSA that were cauterized by bipolar diathermy. Four patients had causative factors, including administration of antiplatelet agents, Valsalva-like manoeuvre, nose blowing and removal of nasal packing, respectively. No patients had recurrent epistaxis during the follow-up period.Post-EETS epistaxis is a rare but severe complication that could lead to catastrophic consequences, and one of the most common bleeding sources is the PNSA. Endoscopic bleeding artery electrocauterization under general anesthesia may be a safe, economic and effective measure for epistaxis refractory to nasal packing. Avoiding excessive downward extension of the septal mucosal incision could contribute to the prevention of postoperative epistaxis.